Uji Kualitatif Senyawa Flavonoid Berbagai Spesies Rumput Laut sebagai Penunjang Perkuliahan Kimia Bahan Alam - Safitri, Amelia Rahmawani; Hakim, Aliefman; Savalas, Lalu Rudyat Telly; Hadisaputra, Saprizal (Chemistry Education Practice, 2023)
This research was exploratory descriptive research that aimed to analyze the types of seaweed that contain flavonoid compounds and compile them into instructions for a chemical practicum of natural product in the form of booklets. The populations in this study were all seaweed species that live in Cemara Beach, Ekas Buana Beach, and Labuhan Haji Beach. The samples were seaweeds which belong to 3 divisions, namely Rhodophyta, Chlorophyta, and Phaeophyta. The number of samples tested in this study was 11 types of seaweeds. The qualitative test methods used were the Willstatter test and the Thin Layer Chromatography (KLT) test. Of the 11 samples tested, it was shown that the types of seaweed that were positive for containing flavonoid compounds were Caulerpa lentilifera, Sargassum crassifolium, Chondrus scrispus, and Eucheuma spinosum. Among four samples positively tested for flavonoids, the type of seaweed that is most found and shows the most obvious stainss was Sargassum crassifolium. This is what underlies the researcher to choose Sargassum crassifolium to be used as a practical guide in the form of a booklet.